Effect of Quenching Media on Corrosion Resistance of Al-Si-Mg Alloy - Dr.Abdulazeez O. Mousa Al-Uqaily, et.al (Al-Qadisiyah Journal of Pure Science, 2017)
This study aims to preparing of Al-Si-Mg alloy and study the effect of quenchingmedia (polymer solution and water) on the properties of prepared alloy such as corrosionresistance in 3.5% NaCl , surface roughness and microstructure. Also study the effect ofaddition alloying elements (Boron and Titanium) on above properties of prepared alloy.The results showed that improvement in corrosion resistance and surface softness ofprepared alloys when addition of boron and titanium to the prepared alloy and whenquenched in polymer solution. Optical microscopic results showed that themicrostructure of prepared alloys when quenched in polymer solution consists of shape,size and uniform distributing for grains in comparison with the same alloys whenquenched in water.